Penerapan Komputer Akuntansi Dengan Aplikasi Si Apik Pada Cv Riharo Mielne - Muhammad Isa Alamsyahbana; Ranat Mulia Pardede; Meidi Yanto; Tiara Wulandari; Vanisa Meifari (Jurnal Mirai Management, 2022)
Based on the research, the formulation of this research is how to apply technology-based financial accounting using the application (SI APIK) on CV Riharo Mielne. The purpose of the study was to determine the application of financial accounting using the technology-based SI APIK application on CV Riharo Mielne. The method used in this study is qualitative, with documentation and observation data collection techniques, the object of this research is CV Riharo Mielne’s business. The benefit of this research is to provide convenience for companies in managing finances using the SI APIK application. The results of this study are that so far CV Riharo Mielne does not prepare financial reports due to the owner's lack of understanding of accounting principles, the preparation of financial reports through the SI APIK application makes financial recording easier and more automatic. It can be concluded that the recording of financial transactions has been simple by CV Riharo Mielne so far through recording cash in, cash out and customer receivable records, by compiling financial records using the SI APIK application. CV Riharo Mielne can arrange financial transactions easily and automatically and can easily print output financial statements. Keywords : MSMEs, financial records, SI APIK